Enhancement of the Safety and Efficiency of Electrical Installations at UKM Kemuning Mandiri to Foster Sustainable Production (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
At UKM Kemuning Mandiri in Cogreg Village, we improved understanding and safety in the operation of electrical devices by introducing a regular maintenance program, providing training, and performing repairs to electrical installations. We identified a lack of knowledge regarding safe electrical installations as the primary cause of work accidents and equipment damage. We utilized training materials to convey the importance of routine maintenance, the safe use of electrical outlets, and standard installation procedures. We assess the existing electrical installation and provide recommendations for enhancement. These recommendations include the installation of supplementary safeguards, such as UPS and stabilizers, to reduce the likelihood of power outages and voltage fluctuations. In order to assist the implementation of the Key Performance Indicators (KPI) of the university, both students and lecturers are involved. These KPIs include the experiences that students have had off campus as well as the involvement of lecturers in community activities. We anticipate that this program will improve students' understanding of electrical safety, decrease the risk of equipment damage, prolong the life of production tools, and boost the productivity of small and medium-sized enterprises. We also anticipate that the maintenance program's sustainability will significantly lower the risk of workplace accidents and equipment damage.